Real-World Comparison of Bezlotoxumab to Standard of Care Therapy for Prevention of Recurrent Clostridioides difficile Infection in Patients at High Risk for Recurrence. (4th August 2021) - Johnson, Tanner M; Molina, Kyle C; Howard, Amanda H; Schwarz, Kerry; Allen, Lorna; Huang, Misha; Bajrovic, Valida; Miller, Matthew A
Abstract : Bezlotoxumab was significantly associated with reduced odds of recurrent Clostridioides difficile infection and all-cause readmission at 90 days on both unadjusted and adjusted analysis. Bezlotoxumab was well tolerated with low frequency of adverse events observed. Abstract: Background: Bezlotoxumab (BEZ) is a monoclonal antibody used to prevent recurrent Clostridioides difficile infection (rCDI). This study investigates BEZ effectiveness in relation to rCDI and patient-specific risk factors in a real-world setting. Methods: A matched, retrospective cohort study was conducted from 2015 to 2019 to compare BEZ to historical standard of care (SoC) therapy with vancomycin or fidaxomicin. The primary outcome was incidence of 90-day rCDI. Secondary outcomes were incidence of all-cause hospital readmission and all-cause mortality at 90 days, infusion-related reactions, and incidence of heart failure exacerbation. Baseline confounding was addressed using inverse probability of treatment weighting (IPTW). Results: Overall, 107 participants were included (54 BEZ and 53 SoC). Mean number of prior CDI episodes was 2, median number of risk factors for rCDI was 4, and 28% of participants had severe CDI. Incidence of 90-day rCDI was 11% BEZ vs 43% SoC ( P = < .001) and 90-day all-cause readmission was 40% BEZ vs 64% SoC ( P = .011). In IPTW-adjusted analyses, BEZ was associated with significantly reduced odds of rCDI (odds ratio [OR], 0.14 [95% confidence interval CI: .05–.41]) and all-cause readmission (OR, 0.36 [95% CI: .16–.81]). No safety signals were detected with BEZ use. Conclusions: BEZ is effective for the prevention of rCDI and reduction in all-cause hospital readmission for patients at high risk for recurrence, supporting current guideline recommendations.